Effect of high pressure carbon dioxide on the browning inhibition of sugar-preserved orange peel. Issue 46 (April 2021) - Zhang, Jiao; Iqbal, Aamir; Murtaza, Ayesha; Zhou, Xuan; Xu, Xiaoyun; Pan, Siyi; Hu, Wanfeng
Highlights: HPCD pretreatment at 9 Mpa could effectively inhibit the browning of processed orange peel. PAL activity significantly decreased with the pressure of HPCD treatment. HPCD treatment effectively reduced Maillard reaction between reducing sugars and amino acids. HPCD application has practical implications for the inhibition of browning. Abstract: In the present study, the effect of high pressure CO2 (HPCD) pretreatment on the browning of reducing sugar-preserved orange peel was evaluated. Fresh orange peel cubes were subjected to different pressures (4, 7.4 and 9 MPa; 31 °C; 20 min). The changes in the browning-related components during the processing (pretreatment, sugar curing, and thermal drying) of preserved orange peel were studied. The results shown HPCD treatment could slow down the enzymatic browning and Maillard reaction in orange peel. Specifically, A significant decrease in PAL activity (p < 0.05) was found in all HPCD-treated samples. The total phenolic compound, free amino acid, and reducing sugar content in the HPCD-treated samples were higher than in the untreated ones. HPCD treatment inhibits the activity of PAL due to the acidic effect of CO2, and reduces the dissolved oxygen inside the tissue during the decompression process, thereby slowing down the enzymatic browning in orange peel; while the interaction of CO2 and basic amino acids protects the alkali amino acids, thereby slowing Maillard reaction during orange peel sugar curing stage. HPCD pretreatment at 9 MPa could effectively inhibit the browning of processed orange peel (p < 0.05). HPCD application under appropriate treatment conditions has practical implications for the inhibition of browning and provides theoretical support for other preserved fruits.